Outcome Analysis Comparing Muscle and Fasciocutaneous Free Flaps for Heel Reconstruction: Meta-Analysis and Case Series - Chellamuthu, Abiramie; Jayaraman, Sathish Kumar; A., Ramesh B. (Indian Journal of Plastic Surgery, 2023)
Background Choosing the components of free flap (fasciocutaneous or muscle) is one of the crucial but controversial decisions in heel reconstruction. This meta-analysis aims to provide an up-to-date comparison of fasciocutaneous flaps (FCFs) and muscle flaps (MFs) for heel reconstruction and to ascertain if one flap has an advantage over the other.Methods Following the Preferred Reporting Item for Systematic Reviews and Meta-Analyses guidelines, a systematic literature review was performed identifying studies on heel reconstruction with FCF and MF. Primary outcomes were survival, time of ambulation, sensation, ulceration, gait, need for specialized footwear, revision procedures, and shear. Meta-analyses and Trial Sequential Analysis (TSA) were performed to estimate the pooled risk ratios (RRs) and standardized mean difference (SMD) with fixed effects and random effects models, respectively.Results Of 757 publications identified, 20 were reviewed including 255 patients with 263 free flaps. The meta-analysis showed no statistically significant difference between MF and FCF in terms of survival (RR, 1; 95% confidence interval [CI], 0.83, 1.21), gait abnormality (RR, 0.55; 95% CI, 0.19, 1.59), ulcerations (RR, 0.65; 95% CI, 0.27, 1.54), footwear modification (RR, 0.52; 95% CI, 0.26, 1.09), and revision procedures (RR, 1.67; 95% CI, 0.84, 3.32). FCF had superior perception of deep pressure (RR, 1.99; 95% CI, 1.32, 3.00), light touch, and pain (RR, 5.17; 95% CI, 2.02, 13.22) compared with MF. Time to full weight-bearing (SMD, –3.03; 95% CI, –4.25, –1.80) was longer for MF compared with FCF. TSA showed inconclusive results for comparison of the survival of flaps, gait assessment, and rates of ulceration.Conclusion Patients reconstructed with FCF had superior sensory recovery and early weight bearing on their reconstructed heels, hence faster return to daily activities compared with MFs. In terms of other outcomes such as footwear modification and revision procedure, both flaps had no statistically significant difference. The results were inconclusive regarding the survival of flaps, gait assessment, and rates of ulceration. Future studies are required to investigate the role of shear on the stability of the reconstructed heels.
Keywords: weight-bearing heel; reconstruction; fasciocutaneous; musculocutaneous